Exploring the Effect of Training in Visual Block Programming for Preservice Teachers - Sáez-López, José Manuel; del Olmo-Muñoz, Javier; González-Calero, José Antonio; Cózar-Gutiérrez, Ramón (Multimodal technologies and interaction, 2020)
This study evaluates the effectiveness of visual block programming-based instruction and its possibilities in the training of future teachers. In particular, the application Scratch, a visual programming environment, was employed to introduce pre-service teachers to programming. The study followed a mixed-method design with a sample of 79 pre-service teachers. A quantitative approach was used to evaluate the gains in the participants’ knowledge of computational concepts and attitudes towards Scratch as a pedagogic tool. A qualitative analysis aimed at evaluating the participants’ knowledge concerning programming applications, and their perception about possible difficulties in the implementation of programming in educational contexts. Positive results were obtained for programming in the classroom, with significant improvements in innovation, collaboration, active learning, motivation, and fun for the students. After the experiment, the subjects highlighted Scratch as a fundamental block programming tool and the need for teacher training in this field. The need to improve the implementation of visual block programming in Education Degree curricula is supported.